Confocal Raman Microscopy for Investigating Synthesis and Characterization of Individual Optically Trapped Vinyl-Polymerized Surfactant Particles. Issue 6 (June 2014) - Schaefer, Jonathan J.; Crawford, Alexis C.; Porter, Marc D.; Harris, Joel M.
Small polymeric particles are increasingly employed as adsorbent materials, as molecular carriers, as delivery vehicles, and in preconcentration applications. The rational development of these materials requires in situ methods of analysis to characterize their synthesis, structure, and applications. Optical-trapping confocal Raman microscopy is a spectroscopic method capable of acquiring information at several stages of the development of such dispersed particulate materials. In the present study, an example material is developed and tested using confocal Raman microscopy for characterization at each stage of the process. Specifically, the method is used to investigate the synthesis, structure, and applications of individual polymeric surfactant particles produced by the vinyl polymerization of sodium 11-acrylamidoundecanoate (SAAU). The kinetics of polymerization can be monitored over time by measuring the loss of the acrylamide C=C functional groups using confocal Raman microscopy of particles optically trapped by the excitation laser, where, within the limits of detecting the vinyl functional group, the complete polymerization of the SAAU monomer was achieved. The polymerized SAAU particles are spherical, and they exhibit uniform access to water throughout their structure, as tested by the penetration of heavy water (D2 O) and collection of spatially resolved Raman spectra from the interior of the particle. These porous particles contain hydrophobic domains that can be used to accumulate molecules for adsorption or carrier applications. This property was tested by using confocal Raman microscopy to measure the accumulation equilibria and kinetics of a model compound, dioxybenzone. The partitioning of this compound into the polymer surfactant could be determined on a quantitative basis using relative scattering cross sections of the SAAU monomer and the adsorbate. The study points out the utility of optical-trapping confocal Raman microscopy for investigating the synthesis, structure, and potential carrier applications of polymeric particle materials.